Clinical Evaluation of an Arthroscopic Knotless Suprapectoral Biceps Tenodesis Technique: Loop 'n' Tack Tenodesis. Issue 6 (22nd June 2018) - Duerr, Robert A.; Nye, Darin; Paci, James M.; Akhavan, Sam
Background: Pathology of the long head of the biceps tendon is a well-known cause of shoulder pain that is commonly managed with arthroscopic suprapectoral biceps tenodesis when conservative treatment fails. Purpose: To present an arthroscopic knotless suprapectoral biceps tenodesis technique known as "Loop 'n' Tack" tenodesis and to report the clinical outcomes of patients with a minimum 2 years of follow-up. Study Design: Case series; Level of evidence, 4. Methods: A retrospective review of all patients who had undergone Loop 'n' Tack tenodesis between January 2009 and May 2014 was completed. Charts were reviewed, and patients were contacted for demographic data, time from surgery, concomitant procedures, and workers' compensation status, as well as visual analog scale for pain, American Shoulder and Elbow Surgeons (ASES), Single Assessment Numeric Evaluation, and University of California, Los Angeles (UCLA) scores. Results: Complete follow-up evaluations were performed for 59 of 68 patients (87%). Mean follow-up was 43 months. A majority (88%) of patients had at least 1 additional procedure performed at the time of biceps tenodesis. The mean ASES shoulder score improved from 42.6 preoperatively to 91.0 postoperatively ( P < .001), and 54 of 59 patients (91.5%) had a good/excellent outcome, with a UCLA shoulder score >27 and ASES shoulder score >70. Three patients (5%) reported biceps cramping pain with overuse, and 2 (3.3%) reported intermittent anterior shoulder pain. No patients had developed a "Popeye" deformity at final clinical examination, and 97% reported that they were overall satisfied with the procedure. Conclusion: The Loop 'n' Tack tenodesis technique results in a high rate of patient satisfaction, significant improvement in shoulder outcome scores, and a low incidence of postoperative pain, with no reoperations for biceps-related pathology.